Evaluation of COVID-19 Virus Effect on Production and Employment of Iranian Economy - Esfandiar Jahangard; Jamal Kakaie (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2021)
The COVID-19 pandemic became widespread in most countries of the world in late 2019. In addition to human casualties, it has also affected the economies of countries. According to IMF, the world economic growth in 2020 was -3.5 percent. However, the GDP’s growth rate of the Iran economy for 2020 has been positive and was reported as 1.5 percent, but there is evident that the economy has been affected by the coronavirus.  In this paper, we evaluate the effect of the COVID-19 pandemic on the production, employment, and value-added of the economy of Iran by using the hypothetical extraction method of Dietzenbacher & Lahr (2013) and the Input-Output general equilibrium model of Zaytseva (2000). We have used the data from the input-output table of the Iran Central Bank in 2016 and the employment figures of the Statistics Center of Iran. The results show that the production and the value-added of the economy will decrease by 4.3 and 4 percent respectively. Among the value-added components, mixed-income and net operating surplus experienced the highest declining growth rate. Also, about 6.5 percent of the country's employees have been affected directly and indirectly by the Coronavirus.